Haemosporidian infections in the Tengmalm's Owl (Aegolius funereus) and potential insect vectors of their transmission - Synek, Petr; Popelková, Alena; Koubínová, Darina; Šťastný, Karel; Langrová, Iva; Votýpka, Jan; Munclinger, Pavel (Parasitology research, 2016)
Sedentary bird species are suitable model hosts for identifying potential vectors of avian blood parasites. We studied haemosporidian infections in the Tengmalm's Owl (Aegolius funereus) in the Ore Mountains of the Czech Republic using molecular detection methods. Sex of owl nestlings was scored using molecular sexing based on fragment analysis of PCR-amplified CHD1 introns. Observed infection prevalences in nestlings and adult owls were 51 and 86 %, respectively. Five parasite lineages were detected. Most of the infections comprised the Leucocytozoon AEFUN02 and STOCC06 lineages that probably refer to distinct Leucocytozoon species. Other lineages were detected only sporadically. Mixed infections were found in 49 % of samples. The main factor affecting the probability of infection was host age. No effect of individual sex on infection probability was evidenced. The youngest infected nestling was 12 days old. High parasite prevalence in the Tengmalm's Owl nestlings suggests that insect vectors must enter nest boxes to transmit parasites before fledging. Hence, we placed sticky insect traps into modified nest boxes, collected potential insect vectors, and examined them for the presence of haemosporidian parasites using molecular detection. We trapped 201 insects which were determined as biting midges from the Culicoides genus and two black fly species, Simulium (Nevermannia) vernum and Simulium (Eusimulium) angustipes. Six haemosporidian lineages were detected in the potential insect vectors, among which the Leucocytozoon lineage BT2 was common to the Tengmalm's Owl and the trapped insects. However, we have not detected the most frequently encountered Tengmalm's Owl Leucocytozoon lineages AEFUN02 and STOCC06 in insects.
Keywords: Sex Factors; Transmission; Ceratopogonidae; prevalence; Strigiformes; Insect Vectors; Wildlife diseases; nemoci ptáků; Female; Vectors; věkové faktory; zvířata; Haemosporida; Protozoan Infections, Animal; sexuální faktory; Blood parasites; Molecular sexing of owls; Avian malaria; ženské pohlaví; hmyz - vektory; Male; polymerázová řetězová reakce; Czech Republic; Polymerase Chain Reaction; Prevalence; Age Factors; Animals; Bird Diseases; Česká republika; mužské pohlaví; protozoální infekce zvířat; Simuliidae; Stringiformes